Diagnostic and clinical approach to a paediatric patient with skin aplasia of the head as a rare manifestation of Xia-Gibbs syndrome caused by a new, potentially pathogenic de novo mutation in the AHDC1 gene - Ręka, Gabriela; Górecki, Mateusz; Wojciechowska, Katarzyna; Lejman, Monika (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Xia-Gibbs syndrome is caused by pathogenic variants in the AHDC1 gene. The characteristic features of the syndrome include delayed psychomotor and speech development, short stature, hypotonia, intellectual disability, structural brain anomalies, and mild facial dysmorphia. A boy came to the Genetic Outpatient Clinic due to skin aplasia of the head, facial dysmorphic changes, syndactyly of the second and third toes, delayed motor development, squamous haemangiomas on the head and face, hypoplasia of tooth enamel, excessively developed subcutaneous tissue, hypotonia, and joint laxity. In next-generation whole-exome sequencing a potentially pathogenic variant c.1913G>A, p.Trp638Ter was detected in a single allele of the AHDC1, resulting in premature termination of the protein. The boy’s parents were not carriers of the lesion. Aplasia of the head’s skin is an extremely rare discovery in the phenotype of patients with Xia-Gibbs syndrome. Next-generation sequencing allowed for an accurate diagnosis and detection of a mutation in the AHDC1 gene.